SURVEY ON ADVISOR INTELLIGENCE THROUGH PURCHASE PATTERNS AND SALES ANALYTICS - Pradhan, Gayatri K; Gollapalli, Sarath; M, JANAKI MEENA; Sp, Syedibrahim (Asian Journal of Pharmaceutical and Clinical Research, 2017)
In mutual fund, an individual or a firm that is in the business of giving advice about securities to clients is an investment advisor. InvestmentÂ advisers are individuals or firms that receive compensation for giving advice on investing in stocks, bonds, mutual funds, or exchange-tradedÂ funds. Investment advisors manage portfolios of securities. Advisors can use new cognitive and analytics capabilities to better understandÂ their clients and needs and have a stronger ability to deepen relationships with a better portfolio. In this paper, we analyze data points for each advisor, and distinguish the best prospects, obtain insight into their experience and credentials, and learn about their portfolio, in otherÂ words, to recognize the pattern of portfolio of the advisors. Such analysis helps the sales people to sell the fund company products to theÂ suitable advisors based on the nature of the product they want to sell. This is done by investigating what kind of products advisors have beenÂ buying, and what kind of products they might be looking for. This helps to increase the sales of the products as sales people will be reachingÂ the appropriate advisors.